Women’s Empowerment in Clarisse La Rue Character from Rick Riordan’s Percy Jackson and the Sea of Monsters - Rahmawati , Putri; Seswita, Seswita (Program Studi Sastra Inggris, 2026)
This study analyzes the representation of women’s empowerment through Clarisse La Rue in Rick Riordan’s Percy Jackson: The Sea of Monsters. The research focuses on the obstacles that hinder Clarisse from empowering herself and the character development she experiences throughout the Golden Fleece quest. Using Betty Friedan’s theory of women empowerment from The Feminine Mystique, this study examines how Clarisse struggles with patriarchal expectations, external pressure, and the need for validation from her father, Ares. This research applies qualitative methods and library research to analyze the novel as the primary source. The findings reveal that Clarisse initially embodies aggressive and competitive traits shaped by patriarchal expectations, yet gradually develops self-awareness and emotional maturity. Through cooperation, vulnerability, and leadership, Clarisse transforms from a stubborn bully into a more empowered and self-aware character.